Application of Plant Biostimulants as New Approach to Improve the Biological Responses of Medicinal Plants- A Critical Review - H Rafiee; HA Naghdi Badi; A Mehrafarin; A Qaderi; N Zarinpanjeh; A Sękara; E Zand (Institue of Medicinal Plants, ACECR, 2016)
The aim of this review was to represent a category of applied plant biostimulants and to highlight the effect of their application on morphological and phytochemical properties of medicinal plants in in vivo and in vitro conditions and their mechanism of action. Plant biostimulants, safe for both human beings and the environment, are substances or materials, except for nutrients and pesticides, which have the ability to beneficially modify plant growth and have been accepted over the past decade. Plant biostimulants have natural and synthetic origin. The natural biostimulants contain amino acids, bacteria, seaweed, yeast, chitosan, phytohormones, and also plant growth regulators (synthetic hormones), phenolic compounds, inorganic salts, essential elements, and other different substances are some examples of synthetic biostimulants. The plant biostimulants through different mechanisms of action (such as nitrogen assimilation) are sustainable management practice for production of medicinal plants, increasing biomass production, and enhancing secondary metabolites synthesis and it is investigated and shown in many studies in recent years. Furthermore, there are many reports on positive effects of biostimulants and elicitors application on medicinal plants in in vitro culture condition. Some products of companies active in the formulation of biostimulants in Iran are mentioned in this review. In conclusion, yield response in medicinal plants to biostimulants application showed that each medicinal plant responds in a different way based on the chemical composition and components of biostimulants, the timing and rate of application.